An investigation into the role that brand growth has played in either enhancing or diluting Sorbet's purposeful corporate climate - Gottschalk, Cindy Ashira (The IIE, 2017)
Sorbet’s is a brand that is grounded in their ‘higher purpose’ of serving and improving the lives of their staff and their customers as opposed to making a profit (Fhur, 2016). However, over the past 2016-2017 period, various Hello Peter posts have stated that Sorbet has “rude and unfriendly staff,” “bad client service,” and has “under-delivered” (Hello Peter, 2017). A brand culture disconnect can be seen, causing a possible rift between Sorbet’s brand identity and brand image (Nead, 2014). With the aforementioned real world problem in mind, this study’s research problem aims to investigate if Sorbet’s corporate culture, The Sorbet Way, has become enhanced or diluted by Sorbet’s brand growth, and to what extent Sorbet’s current corporate climate has had on Sorbet’s brand image. The rationale behind the research problem is based on how great brands do not just ‘exist’ or ‘happen’, great brands are the product of its people, as a brand’s employees are the ones that are able to bring the brand to life (Nead, 2014). The framework, which was used for this research paper, is the Vision-Culture-Image (VCI) Alignment model proposed by Mary Jo Hatch and Majken Schulz (2008). The methodology used for the study followed a constructivist research paradigm and was based on a qualitative case study research design that had a cross sectional time horizon. Key findings of the study showed that to a large extent, Sorbet is aligned to the VCI model. However, prominent factors, such as the reasoning as to why Sorbet was sold to Long4Life, may have caused gaps within the model.
Keywords: Brand Culture; Brand Identity; Brand Image; Vision-Culture-Image; Corporate Culture